Biology and management of the insect pest threatens global maize production, fall armyworm, Spodoptera frugiperda: an Africa and Asia perspective - Ibrahim Sani; Mohammed Suleiman; Abubakar Samaila; Abbati Nasiru; Kabir Abdullahi Bindawa; Aminu Musa; Zakariya Sani (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2025)
Fall armyworms, Spodoptera frugiperda (J./E. Smith) are among the most serious insect pests in maize and many other crops, particularly in some Asian countries and sub-Saharan Africa. The study aimed to explores the significance of the biological characters and the management strategies to reduce damage caused by FAW. Understanding this destructive insect pest will guide maize growers and agricultural professionals to develop the most effective and sustainable FAW control methods. The caterpillar fed on the leaves and interferes with pollination and fertilization processes, significantly reducing the yield losses in maize, which was one of the main staple food for most smallholder farmers in Africa. Due to their immediate action, synthetic chemical pesticides were the most conventionally used in the control of FAW, even though this method had many weaknesses, including environmental pollution, food safety concerns, insecticide resistance, and effects on non-target organisms. In recent years, biological control agents (BCAs) have been developed as an alternative to the conventional use of chemical pesticides in integrated pest management (IPM) systems of FAW pests. The present BCAs of FAW were parasitoids, predators, and entomopathogens.